The philosophical foundations of 'health for all' and Universal Health Coverage - Luke N. Allen (BMC, 2022)
Abstract The WHO constitution calls for 'health for all' and Universal Health Coverage has been called "the ultimate expression of fairness", however it is not always clear how health systems can move towards equity. Should we prioritise the needs of the worst off? And if so, should we direct resources to these marginalised groups or marginalised individuals? This article provides an overview of the philosophical underpinnings of health equity and proportionate universalism, highlighting the trade-offs involved in operationalising a core tenant of global health practice.